Information Services Through the Trait And Factor Approach to Improve Student Career Planning - Noperlis, Anggi Dwi; Firman, Firman; Netrawati, Netrawati (Widyagogik, 2023)
In improving career planning for students as a teacher, they must be able to choose which services and approaches to use. Information services are one of the services that help individuals get a variety of new information. through the trait and factor approach in information services helps students get information, especially in the career field. So that students are able to plan their career in the future. In this study, the aim was to determine students' understanding of career planning through information services using the trait and factor approach. The method used is by analyzing the literature review, in this case, the researcher analyzed previous studies. The results of the study found that information services through the trait and factor approach were effective in improving student career planning.